Inclusive Interpretation of Sex, Gender and Sexuality Versus Sexual Violence against Women (Global Journal of Human-Social Science, 2013)
Sexual violence against women despite being highly condemned and goddamned in most places, why continues to be an alarmingly endemic and pandemic issue, raises a substantial gender query. This article explores an analytical connection that persists between the inclusive interpretation of sex, gender and sexuality, on the most typical way, and the actuality of human sexual violence, on the strange. This study discloses that the masculine heterosexual and gender interpretation of sex and sexuality perpetuates such violence. The dimensions and factors for sexual abuse/ violence are structured and processed such ways that female gender is often desecrated by men, homosexuals or lesbians are despised by heterosexuals, and feminine submissiveness is violently abused by masculine aggressiveness in different social settings. To demystify the gendered activated stock-still violence against women a sexual exploitation/violence specific based on hetero and non-hetero sexual orientations in cross Figure format has been creatively endeavoured in this article. Our study also tresses that since sexual violence of basic nature going tougher/ complicated with newer individual findings/ interpretations at present context, the researchers have to develop a theoretical comprehensive perspective on the entire gospel of sexual violence against women that has been persisting across global regions, religions, races, etc.
Keywords: gender; sex; sexuality; violence; exploitation